2014
DOI: 10.1007/s13181-013-0368-x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Toxicity after Lighting Coals at a Hookah Bar

Abstract: In recent years, hookah bars have gained in popularity, especially in urban areas and around college campuses. This was the first case to identify the potential occupational exposure of employees working at hookah bars to CO. Furthermore, the patient's COHb level of 33.8 % was higher than any previously reported in the literature with exposure via hookah pipe. The practitioner should consider CO poisoning in patients who smoke tobacco via a hookah and consider early hyperbaric oxygen therapy in those experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…CO has been implicated to play a major role in a multitude of cardiovascular and airway diseases, including atherosclerosis,36 37 cardiomyopathy,38 chronic obstructive pulmonary disease,39 respiratory infections,40 asthma41 and cystic fibrosis 42. CO poisoning after hookah smoking has already been found in a number of case reports, with users presenting carboxyhaemoglobin levels 34% higher than normal after hookah use,43 44 syncope45 and confusion 46. It has been suggested that CO intoxication due to hookah smoking is likely to be more common than that was realised due to inefficient charcoal burning 30 47.…”
Section: Discussionmentioning
confidence: 99%
“…CO has been implicated to play a major role in a multitude of cardiovascular and airway diseases, including atherosclerosis,36 37 cardiomyopathy,38 chronic obstructive pulmonary disease,39 respiratory infections,40 asthma41 and cystic fibrosis 42. CO poisoning after hookah smoking has already been found in a number of case reports, with users presenting carboxyhaemoglobin levels 34% higher than normal after hookah use,43 44 syncope45 and confusion 46. It has been suggested that CO intoxication due to hookah smoking is likely to be more common than that was realised due to inefficient charcoal burning 30 47.…”
Section: Discussionmentioning
confidence: 99%
“…Sidestream hookah smoke contains 30 times the amount of CO as a single cigarette and CO levels within the ambient environment of hookah bars can be as high as 50 ppm (Daher, 1994; Zhou, 2014). In addition, several cases of acute symptomatic CO poisoning have been reported in teenagers and young adults following water pipe use (La Fauci, 2012; Misek, 2014; von Rappard, 2014). CO toxicity in these cases manifested with syncope or loss of consciousness (La Fauci, 2012; Misek, 2014; von Rappard, 2014).…”
Section: Environmental Co and Overt Toxicitymentioning
confidence: 99%
“…In addition, several cases of acute symptomatic CO poisoning have been reported in teenagers and young adults following water pipe use (La Fauci, 2012; Misek, 2014; von Rappard, 2014). CO toxicity in these cases manifested with syncope or loss of consciousness (La Fauci, 2012; Misek, 2014; von Rappard, 2014). Thus, hookah use is rapidly becoming a public health issue and combustion of water pipe tobacco is a significant source of indoor CO pollution in certain environments.…”
Section: Environmental Co and Overt Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have demonstrated hazardous occupational exposures in hookah bars . A study evaluating the indoor air quality in 17 Virginia waterpipe cafés showed high fine particulate matter (PM) 2.5 concentrations in all smoking rooms .…”
mentioning
confidence: 99%